PENGGUNAAN MEDIA PEMBELAJARAN OLEH PENDIDIK PAK SEMESTER GENAP TA 2016-2017 DI STT KRISTUS ALFA OMEGA SEMARANG - Yulia, Tantri (Shift Key : Jurnal Teologi dan Pelayanan, 2017)
The use of instructional  media is related to the suitability of various things, among others: learning objectives, learning materials,  characteristics of learners,  learning theories, learning styles of learners,  environmental conditions, support facilities, time available, cost, organizational support, participant  learning style educate and environmental conditions. Compatibility with other things also supports the effective use of media, but has not been discussed in this study. Educators in the "Christian  Religion" study program have a responsibility to complement their learning with a supportive medium of instruction. Based on the mean anallisa,  "The Use of Learning Media by PAK Educational  Prgram  Educator at STT" Christ Alfa Omega "Semarang is in very high category. Based on the percentage analysis of things that need to be improved is the educator using instructional media in accordance with the characteristics of learners,  learning theory, learning styles, environmental conditions and costs and organizational support needs to be improved